Room-temperature spin-orbit torque in NiMnSb - Ciccarelli, C.; Anderson, L.; Tshitoyan, V.; Ferguson, A.J.; Gerhard, F.; Gould, C.; Molenkamp, L.W.; Gayles, J.; Železný, J.; Šmejkal, L.; Yuan, Z.; Sinova, Jairo; et al. (Nature Publishing Group, 2016)
Materials that crystalize in diamond-related lattices, with Si and GaAs as their prime examples, are at the foundation of modern electronics. Simultaneously, the two atomic sites in the unit cell of these crystals form inversion partners which gives rise to relativistic non-equilibrium spin phenomena highly relevant for magnetic memories and other spintronic devices. When the inversion-partner sites are occupied by the same atomic species, electrical current can generate local spin polarization with the same magnitude and opposite sign on the two inversion-partner sites. In CuMnAs, which shares this specific crystal symmetry of the Si lattice, the effect led to the demonstration of electrical switching in an antiferromagnetic memory at room temperature. When the inversion-partner sites are occupied by different atoms, a non-zero global spin-polarization is generated by the applied current which can switch a ferro-magnet, as reported at low temperatures in the diluted magnetic semiconductor (Ga,Mn)As. Here we demonstrate the effect of the global current-induced spin polarization in a counterpart crystal-symmetry material NiMnSb which is a member of the broad family of magnetic Heusler compounds. It is an ordered high-temperature ferromagnetic metal whose other favorable characteristics include high spin-polarization and low damping of magnetization dynamics. Our experiments are performed on strained single-crystal epilayers of NiMnSb grown on InGaAs. By performing all-electrical ferromagnetic resonance measurements in microbars patterned along different crystal axes we detect room-temperature spin-orbit torques generated by effective fields of the Dresselhaus symmetry. The measured magnitude and symmetry of the current-induced torques are consistent with our relativistic density-functional theory calculations.